Dedicated to the people of Darfur : writings on fear, risk, and hope - Reynolds, Luke, 1980-; Reynolds, Jennifer, 1981- (Rutgers University Press, 2009)
Life's changes. They happen every day. Some large, some small. A few are very personal. Others impact the world. Dedicated to the People of Darfur: Writings on Fear, Risk, and Hope includes original and inspiring essays that celebrate the glories gained from taking risks, breaking down barriers, and overcoming any obstacles. Nobel and Pulitzer Prize winners, a gallery of O. Henry award recipients, and many best-selling authors come together to share personal and compelling challenges and experiences. From contemplations on past drug use to reflections on gun control, social justice, passion and.